Formal Decisions, Informed Futures: A Study of How Decision-Making Processes and Controls Shape Organizational Learning in Knowledge-Intensive Firms - Hedén,Thelma; Svensson,Oscar (2025)
Title: Formal Decisions, Informed Futures: A Study of How Decision-Making Processes and Controls Shape Organizational Learning in Knowledge-Intensive Firms Hand in date: 27th May 2025 Seminar date: 4th June 2025 Course: BUSN79 Degree Project in Accounting and Finance Authors: Thelma Hedén & Oscar Svensson Advisor: Anders Anell Examiner: Liesel Klemcke Five Keywords: Decision-Making, Organisational Learning, Management Control Systems, Formalization, Knowledge-Intensive Firms Purpose: The purpose of the thesis is to study how organizations compile and utilize information from earlier decisions and projects through MCS to drive organizational learning and strengthen future decision-making. Methodology: The methodology is qualitative and explorative to its approach, constituted of a comparative interview study. The data were gathered through semi-structured interviews with managers and consultants involved in the decision-making process within consultancies or production firms, which were then analyzed comparatively. Theoretical perspectives: The theoretical framework consists of a comprehensive literature review of three main areas; decision-making, organizational learning and management control, where the use of management control is assessed based on their direct and indirect nature. Empirical foundation: The empirical findings collected through semi-structured interviews are presented to explain the decision-making process and organizational learning in these knowledge-intensive firms. To further present and analyze the degree of formalization and use of controls in these processes. Conclusions: Knowledge-intensive organizations present different degrees of formalization in their decision-making processes by the usage of direct control and indirect control, in order to drive organizational learning and strengthen future decision-making.
Keywords: Decision-Making; Organisational Learning; Management Control Systems; Formalization; Knowledge-Intensive Firms